Maintenance treatment with buprenorphine and naltrexone for heroin dependence in Malaysia: a randomised, double-blind, placebo-controlled trial. - Schottenfeld, Richard S; Chawarski, Marek C; Mazlan, Mahmud (Lancet, 2008)
Expansion of access to effective treatments for heroin dependence is a worldwide health priority that will also reduce HIV transmission. We compared the efficacy of naltrexone, buprenorphine, and no additional treatment, in patients receiving detoxification and subsequent drug counselling, for maintenance of heroin abstinence, prevention of relapse, and reduction of HIV risk behaviours.
Keywords: Adult; Buprenorphine; Counseling; Double-Blind Method; Heroin Dependence; HIV Infections; Humans; Malaysia; Naltrexone; Narcotic Antagonists; Recurrence; Risk-Taking; Treatment Outcome